2007
DOI: 10.1158/1055-9965.epi-06-1062
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin-like Growth Factor (IGF)-I and IGF-Binding Protein-3 Concentrations and Prostate Cancer Risk: Results from the European Prospective Investigation into Cancer and Nutrition

Abstract: Background: Some studies suggest that elevated serum insulin-like growth factor (IGF)-I concentrations are associated with an increased risk of prostate cancer and, in particular, with an increased risk of advanced-stage prostate cancer. Methods: We analyzed the association between prediagnostic serum concentrations of IGF-I and IGF-binding protein-3 (IGFBP-3) and prostate cancer risk in a case-control study nested in the European Prospective Investigation into Cancer and Nutrition. This study includes 630 inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
3
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 90 publications
(86 citation statements)
references
References 28 publications
5
76
3
2
Order By: Relevance
“…Intervention studies have also shown that protein restriction can lower IGF-I levels in both animals (Miura et al, 1992;Takenaka et al, 2000;Katsumata et al, 2002) and humans (Smith et al, 1995), and that the increases in IGF-I levels following re-feeding are strongly related to the essential amino-acid component of the diet (Clemmons et al, 1985). The effects of protein and especially dairy protein on IGF-I could be important, because high serum IGF-I levels have been associated with a moderately increased risk of prostate cancer in several large-scale prospective studies including EPIC (Renehan et al, 2004;Allen et al, 2007). However, few studies have reported on protein intake in relation to risk (Severson et al, 1989;Schuurman et al, 1999;Chan et al, 2000), and, to our knowledge, this is the first study to examine specifically the association of dairy protein in risk.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies have also shown that protein restriction can lower IGF-I levels in both animals (Miura et al, 1992;Takenaka et al, 2000;Katsumata et al, 2002) and humans (Smith et al, 1995), and that the increases in IGF-I levels following re-feeding are strongly related to the essential amino-acid component of the diet (Clemmons et al, 1985). The effects of protein and especially dairy protein on IGF-I could be important, because high serum IGF-I levels have been associated with a moderately increased risk of prostate cancer in several large-scale prospective studies including EPIC (Renehan et al, 2004;Allen et al, 2007). However, few studies have reported on protein intake in relation to risk (Severson et al, 1989;Schuurman et al, 1999;Chan et al, 2000), and, to our knowledge, this is the first study to examine specifically the association of dairy protein in risk.…”
Section: Discussionmentioning
confidence: 99%
“…All hormone assays were performed by the Laboratory of the Hormones and Cancer Team at the International Agency for Research on Cancer, Lyon, France, by using commercially available immunoassays as described previously (21,22). In brief, Δ4 and ADIOL were measured by radio-immunoassay (RIA) with a double antibody system for the separation of free and bound antigen (Diagnostic Systems Laboratory, Webster, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Androgens are required for the growth, maturation and differentiation of the prostate gland (224,225) It has thus been suggested that testosterone may promote prostate tumour development but may also help maintain prostate tumour differentiation (226) , which may explain why obese individuals with low testosterone levels have a higher risk of developing undifferentiated tumours (222,223) . Other mechanisms that may link obesity with prostate cancer may include high insulin levels, high bioavailable IGF-1 levels, high leptin levels or low adiponectin levels, although most prospective studies on this topic have provided inconsistent results (67,(227)(228)(229)(230)(231)(232)(233)(234)(235)(236) . Also, these latter hormonal mechanisms may not easily explain the difference in the association between obesity and low-grade early-stage disease compared with its association with high-grade late-stage disease.…”
Section: Obesity and Prostate Cancermentioning
confidence: 99%